The Neurovascular Unit: Effects of Brain Insults During the Perinatal Period - Bell, Alexander H. (Front Neurosci, 2020)
The neurovascular unit (NVU) is a relatively recent concept in neuroscience that broadly describes the relationship between brain cells and their blood vessels. The NVU incorporates cellular and extracellular components involved in regulating cerebral blood flow and blood–brain barrier function. The NVU within the adult brain has attracted strong research interest and its structure and function is well described, however, the NVU in the developing brain over the fetal and neonatal period remains much less well known. One area of particular interest in perinatal brain development is the impact of known neuropathological insults on the NVU. The aim of this review is to synthesize existing literature to describe structure and function of the NVU in the developing brain, with a particular emphasis on exploring the effects of perinatal insults. Accordingly, a brief overview of NVU components and function is provided, before discussion of NVU development and how this may be affected by perinatal pathologies. We have focused this discussion around three common perinatal insults: prematurity, acute hypoxia, and chronic hypoxia. A greater understanding of processes affecting the NVU in the perinatal period may enable application of targeted therapies, as well as providing a useful basis for research as it expands further into this area.